A giant [8+12] boronic ester cage with 48 terminal alkene units in the periphery for postsynthetic alkene metathesis - Hähsler, Martin; Mastalerz, Michael (Chemistry - a European journal, 2021)
Dynamic covalent chemistry (DCC) is a powerful synthetic tool to construct large defined molecules in one step from rather simple precursors. The advantage of the intrinsic dynamics of the applied reversible reaction steps is a self-correction under the chosen conditions, to achieve high yields of the target compound. To date, only a few examples are known, in which DCC was used to build up a molecular defined but larger product that was chemically transferred to a more stable congener in a second (irreversible) step. Here, we present a nanometer-sized [8+12] boronic ester cage containing 48 peripheral terminal alkene units which allows to put a hydrocarbon exoskeleton around the cage via alkene metathesis.